Chiral photocurrent in a Quasi-1D TiS3 (001) phototransistor. (29th March 2023) - Gilbert, Simeon J; Li, Mingxing; Chen, Jia-Shiang; Yi, Hemian; Lipatov, Alexey; Avila, Jose; Sinitskii, Alexander; Asensio, Maria C; Dowben, Peter A; Yost, Andrew J
Abstract: The presence of in-plane chiral effects, hence spin–orbit coupling, is evident in the changes in the photocurrent produced in a TiS3 (001) field-effect phototransistor with left versus right circularly polarized light. The direction of the photocurrent is protected by the presence of strong spin–orbit coupling and the anisotropy of the band structure as indicated in NanoARPES measurements. Dark electronic transport measurements indicate that TiS3 is n-type and has an electron mobility in the range of 1–6 cm 2 V −1 s −1 . I – V measurements under laser illumination indicate the photocurrent exhibits a bias directionality dependence, reminiscent of bipolar spin diode behavior. Because the TiS3 contains no heavy elements, the presence of spin–orbit coupling must be attributed to the observed loss of inversion symmetry at the TiS3 (001) surface.